Cylinder segment mount modification to reduce cylinder segment downtime problems on curing machines - Yusuf Nugroho; Subekti Subekti (JTTM : Jurnal Terapan Teknik Mesin, 2024)
In tire manufacturing companies in Indonesia, there is a tire production process consisting of material, building, curing, and final inspection. The curing process is the process of changing green tires into tires which takes place in a mold segment at temperature and pressure according to predetermined specifications. On the BOM 63.5 curing press machine there is a segmented cylinder that functions to press the mold segment. The problem that often occurs in curing machines is that the segment cylinder breaks. This causes quite high machine downtime. The number of cylinder segment bolt holes influences the strength of the bolt connection. Therefore, it is necessary to modify the cylinder segment bolt-hole holder so that the bolt can support the cylinder load. The results of this modification can reduce curing machine downtime problems and can increase company productivity. Based on the results of this research, it can be concluded that 6 bolts are safer than 4 bolts. The downtime problem of the cylinder segment after modification decreased by 94%. The previous one was 15181.18 minutes to 1038.11 minutes